(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
A uniform Goods and Service Tax for the entire nation was first proposed in the union budget of 2007-08. This uniform GST was intended at reducing the cascading effect of indirect taxes levied on sale of goodsservices so that our sales and service taxation system can be simplified for ease of doing business. GST which was initially intended to be introduced with effect from April 1, 2010 is now expected to be implemented from 1st July 2017.For GST to be success every trader should be aware about the new GST rules and regulations. This study measured the awareness and perception of retail traders towards the GST in Kottayam district. This study has revealed that only 32 of the traders are aware about GST and the balances 68 are unawareindifferent about GST. This study also revealed that only 43 of traders presume GST to be beneficial.